Introduction and validation of the Modern adolescent dating violence attitude (MADVA) scale: a contemporary tool for assessing adolescent attitudes towards dating violence in offline and online environments - Kirkman, Gill (International journal of law, crime and justice, 2025)
The study developed and validated the Modern Adolescent Dating Violence Attitude (MADVA) scale, examining young people's attitudes towards online and offline variants of adolescent dating violence and abuse (ADVA). Data were collected among 2011 adolescents from England, aged 10-25 (M 15.72 years). Dimensionality and construct validity of the MADVA was investigated using traditional Confirmatory Factor Analysis. Results indicate a six-factor model (Attitudes towards: Sexual Abuse-Online; Sexual Abuse-Offline; Psychological Abuse-Online; Psychological Abuse-Offline; Physical Abuse-Offline; Controlling Behaviour-Offline). Excellent composite reliability and differential predictive validity were observed for all six subscales. The MADVA scale enables users to better evaluate ADVA prevention-programmes.